Transcriptomic analysis of the upper lip and primary palate development in mice - Cai, Sini; Si, Nuo; Wang, Yanyang; Yin, Ningbei (Frontiers in Genetics, 2023)
Background: Normal fusion of the upper lip and primary palate is a complex process involving a series of characteristic and orderly regulated cellular events. Cleft lip with or without palate (CL/P), one of the most common congenital malformations, may be induced by abnormalities in any of these events. However, less is known about the precise regulatory process in the fusion of the upper lip and primary palate. Methods: Lambdoidal junction tissues of mice from embryonic days 10.5, 11.5, and 12.5— three key fusion stages—were acquired for RNA sequencing. Results: Gene expression profiles in distinct fusion stages of mice were identified. Some of the differentially expressed genes (DEGs) have been reported to affect upper lip and primary palate development. However, other DEGs, such as Krt5, Pax1, Ambn, Hey2, and Tnmd, have not previously been investigated. Gene set enrichment analysis (GSEA) of these DEGs revealed the sequential intensification of Wnt, PI3K-Akt, MAPK, Hippo, and TGF-beta signaling pathways and identified relatively highly expressed genes including Tnn, Wnt3a, and Wnt16. We also observed substantial alternative splicing events during the fusion of the upper lip and primary palate and identified potentially important genes including Gtpbp8, Armcx1, Tle3, and Numa1. Protein-protein interaction (PPI) network analysis identified a series of hub genes, including Col1a2, Fos, Bmp2, Shh, Col1a1, Wnt3a, Anxa1, Gem, etc. Conclusion: Overall, the results of this study provided a comprehensive analysis of the development of the upper lip and primary palate. Our work provides insight into future studies of normal upper lip and primary palate development and the etiology of CL/P.